Model Pembelajaran Role Playing Dalam Meningkatkan Minat Belajar Pada Siswa Mata Pelajaran Pendidikan Penerapan Agama Kristen Di SD Smart School Jakarta Utara - Hia, elpin Putriani; Michael, Michael (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract The background of this research is that in the learning process teachers still use the lecture method. This makes students bored and not enthusiastic about learning, so that students' interest in learning is low. Interest is a sense of liking, a sense of being interested in something. In the learning process the teacher must have a creativity, so that students have an interest in learning. One of the things that teachers do is use a learning model. Where the teacher must apply the role playing learning model in increasing interest in learning in students of Christian Religious Education subjects. Therefore, a study was conducted to answer the formulation of the problem, namely whether the application of the role playing learning model increases interest in learning in Christian Religious Education subjects at SD Smart School, North Jakarta. To answer the formulation of the problem, the author conducted research on the application of the role playing learning model in increasing interest in learning in Christian Religious Education subjects at SD Smart School, North Jakarta. After conducting research, it was found that there was a relationship between the role playing learning model in increasing interest in learning in Christian religious education subjects of 0.788 and this relationship was classified as strong. In addition to the relationship between the two, it was also found that the role playing learning model had an influence or contributed to increasing interest in learning in Christian Religious Education subjects by 0.621 or 62% and 38% and the rest was influenced by other factors. Keywords: Role Playing Learning Model and Interest in Learning in Christian Religious Education subjects at SD Smart School, North Jakarta.